A phase I single ascending dose safety study of NTRX‐07 in normal volunteers: Human/Human trials: Inflammation. (7th December 2020) - Foss, Joseph; Naguib, Mohamed; Giordano, Tony
Abstract: Background: NTRX‐07 is a selective cannabinoid receptor type 2 (CB2 ) agonist that has been shown in animal models to be effective for the treatment of Alzheimer's disease (AD). CB2 agonists have been shown to be neuroprotective in preclinical models and the lack the psychotropic adverse effects normally seen with CB1 agonists 1‐4 . NTRX‐07 has acceptable drug metabolism, pharmacokinetic and preclinical safety profiles. Method: This is a double‐blind, placebo controlled single ascending dose study with 6 cohorts of normal volunteers 18‐65 years of age (n=∼48). The primary outcome is the safety and tolerability of NTRX‐07. Each cohort is randomized with 6 subjects receiving active drug and 2 placebo. Doses range from 0.3 to 8 mg/kg of NTRX‐07 in a HPMCAS‐MG excipient administered orally. Subjects are admitted to the site the night before dosing, and are observed for 24 hours post‐dose, with a safety visit 7 days later. Subjects are observed for changes in physical exam or symptoms (including questionnaires of drug effect), vitals, laboratory values and adverse events (AEs). Blood samples are obtained to determine the pharmacokinetics of NTRX‐07 in humans. Result: At submission three cohorts have completed dosing and all cohorts will be completed for final poster submission. No treatment related AEs have been observed. Plasma levels have been higher than predicted based on preclinical studies suggesting differences in absorption or metabolism compared to animal models. Pharmacokinetics (PK) have demonstrated dose linearity and support feasibility in clinical use. Conclusion: There are currently no commercially available CB2 agonists. NTRX‐07 would represent the first‐in‐class of a new therapeutic agent to treat microglial‐mediated neuroinflammation in a variety of diseases where the CB2 receptor has been shown to be active such as AD, ALS and FTD. The next study will be a 28 day repeat dose of NTRX‐07, in patients with MCI or early AD, for safety, PK and exploratory biomarkers. References: 1 Naguib, M. et al. Br. J. Pharmacol. 155, 1104‐1116 (2008). 2 Diaz, P. et al. ChemMedChem 4, 1615‐1629 (2009). 3 Wu, J. et al . Neurobiol. Aging 34, 791‐804 (2013). 4 Wu, J., et al. Eur. J. Pharmacol. 811, 12‐20, (2017).